A policeman remembers : memoirs of Herbie Jayasuriya (retired senior superintendent of police). (Ratmalana : Vishva Lekha, 1999)
Autobiographical account of a former senior superintendent of police, Sri Lanka.
Keywords: Police chiefs -- Sri Lanka -- Biography; Police -- Sri Lanka -- Biography